2011
DOI: 10.1096/fj.10-168633
|View full text |Cite
|
Sign up to set email alerts
|

Local cholesterol increase triggers amyloid precursor protein‐Bacel clustering in lipid rafts and rapid endocytosis

Abstract: Amyloid peptide (Aβ) is generated by sequential cleavage of the amyloid precursor protein (APP) by β-secretase (Bace1) and γ-secretase. Aβ production increases after plasma membrane cholesterol loading through unknown mechanisms. To determine how APP-Bace1 proximity affects this phenomenon, we developed a fluorescence lifetime imaging microscopy-Förster resonance energy transfer (FLIM-FRET) technique for visualization of these molecules either by epifluorescence or at the plasma membrane only using total inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 54 publications
8
137
0
Order By: Relevance
“…Moreover, cholesterol might be involved in this. Recently, it has been reported that cholesterol increases ␤-secretase processing of APP by triggering APP-BACE1 clustering into lipid rafts, preceded by rapid endocytosis (79). Indeed, we found that DHA changes the raft/non-raft distribution of cholesterol, and thus one might speculate that DHA reduces secretase activities by affecting cholesterol levels in lipid raft microdomains, resulting in reduced internalization to the endosomal system, which is discussed to be important for amyloidogenic processing of APP (80).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, cholesterol might be involved in this. Recently, it has been reported that cholesterol increases ␤-secretase processing of APP by triggering APP-BACE1 clustering into lipid rafts, preceded by rapid endocytosis (79). Indeed, we found that DHA changes the raft/non-raft distribution of cholesterol, and thus one might speculate that DHA reduces secretase activities by affecting cholesterol levels in lipid raft microdomains, resulting in reduced internalization to the endosomal system, which is discussed to be important for amyloidogenic processing of APP (80).…”
Section: Discussionmentioning
confidence: 52%
“…Cholesterol depletion also decreases the association of BACE1 with lipid rafts resulting in decreased processing of APP (Ehehalt, Keller, Haass, Thiele, & Simons, 2003; Hattori et al, 2006; Riddell, Christie, Hussain, & Dingwall, 2001). By contrast, acute cell exposure to cholesterol promotes the coclustering of APP and BACE1 in lipid raft domains, as well as their rapid endocytosis (Marquer et al, 2011). Introduction of a glycosylphosphatidylinositol anchor, a targeting motif for lipid raft localization, into the BACE1 sequence strongly promotes amyloidogenic processing of APP (Hartmann et al, 2007; Simons et al, 1998), further supporting the key role of the BACE1 association in Aβ generation.…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…Using an enzymatic assay that quantifies both free cholesterol and cholesteryl esters, Xiong et al (2008) demonstrated that AD brain extracts contain more cholesterol than control brains and that this may contribute to high β-and γ-secretase activities and Aβ production in AD. More recently, however, a study by Marquer et al (2011) showed that plasma membrane cholesterol content, measured by a fluorescence lifetime imaging microscopy-Förster resonance energy transfer technique, does not increase cellular Aβ production by having a direct impact on BACE1 catalytic activity but rather by altering the accessibility of BACE1 to its substrate, APP. This change in accessibility of APP to BACE1 is mediated by clustering in lipid rafts, followed by rapid endocytosis (Marquer et al, 2011).…”
Section: Alzheimer's Disease -The Role Of Lipid Metabolism and Endocymentioning
confidence: 99%
“…More recently, however, a study by Marquer et al (2011) showed that plasma membrane cholesterol content, measured by a fluorescence lifetime imaging microscopy-Förster resonance energy transfer technique, does not increase cellular Aβ production by having a direct impact on BACE1 catalytic activity but rather by altering the accessibility of BACE1 to its substrate, APP. This change in accessibility of APP to BACE1 is mediated by clustering in lipid rafts, followed by rapid endocytosis (Marquer et al, 2011).…”
Section: Alzheimer's Disease -The Role Of Lipid Metabolism and Endocymentioning
confidence: 99%